2010
DOI: 10.1161/circinterventions.109.917070
|View full text |Cite
|
Sign up to set email alerts
|

Iodixanol Versus Low-Osmolar Contrast Media for Prevention of Contrast Induced Nephropathy

Abstract: Background-Contrast-induced nephropathy (CIN) is associated with significant morbidity and mortality. The objective of our meta-analysis was to assess the efficacy of iodixanol compared with low-osmolar contrast media (LOCM) for prevention of CIN. Methods and Results-We searched MEDLINE, the Cochrane Central Register of Controlled Trials, and internet sources of cardiology trial results for individual and relevant reviews of randomized, controlled trials, for the terms contrast media, contrast nephropathy, ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 56 publications
3
65
1
3
Order By: Relevance
“…The disparate results of these previous 14 clinical trials led to a proliferation of systematic reviews and meta-analyses comparing the nephrotoxicity of IOCM iodixanol and various LOCM; five of which have now been published [32,[62][63][64][65][66] . Among earlier meta-analyses by McCullough et al [62] , pooled data from 2727 patients from 16 doubleblind, RCTs have indicated that use of the IOCM iodixanol is associated with smaller rises in creatinine and lower rates of RCIN than LOCM (1.4% vs 3.5%, P < 0.001), especially in patients with CKD or CKD and diabetes mellitus.…”
Section: Type Of Contrast Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The disparate results of these previous 14 clinical trials led to a proliferation of systematic reviews and meta-analyses comparing the nephrotoxicity of IOCM iodixanol and various LOCM; five of which have now been published [32,[62][63][64][65][66] . Among earlier meta-analyses by McCullough et al [62] , pooled data from 2727 patients from 16 doubleblind, RCTs have indicated that use of the IOCM iodixanol is associated with smaller rises in creatinine and lower rates of RCIN than LOCM (1.4% vs 3.5%, P < 0.001), especially in patients with CKD or CKD and diabetes mellitus.…”
Section: Type Of Contrast Agentsmentioning
confidence: 99%
“…However, iodixanol was associated with a lower incidence of RCIN compared with ioxaglate and iohexol, but not when compared with other LOCM. In the most recent meta-analysis, which included 36 trials encompassing 7166 patients, From et al [65] compared iodixanol to several LOCMs. They found that iodixanol had no statistically significant reduction in RCIN incidence below that observed with heterogeneous comparator agents (P = 0.11).…”
Section: Type Of Contrast Agentsmentioning
confidence: 99%
“…However, both strategies are inappropriate in terms of patient safety. On one hand, higher concentrations of iodine contrast agent may lead to an increased burden in the patients' hematological and urinary systems [15]. On the other hand, higher X-ray energy is also not practical due to radiation dose limitations, especially since the liver is radiation-sensitive, and liver CTPI requires multiple acquisitions of the same region.…”
Section: Introductionmentioning
confidence: 99%
“…Today, we can choose between iodixanol, the only IOCM presently approved for intravascular administration, and an array of LOCM, such as the widely used iopamidol. Current guidelines leave this choice to the physician [1,[6][7][8], because the results of prospective clinical head-to-head comparisons concerning the renal safety of iodixanol versus LOCM have been contradictory [2,[9][10][11][12]. One major reason behind this lack of consistent results is that the vast majority of clinical studies have been relying on serum creatinine concentration (SCrea) as the sole end point [2,9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Current guidelines leave this choice to the physician [1,[6][7][8], because the results of prospective clinical head-to-head comparisons concerning the renal safety of iodixanol versus LOCM have been contradictory [2,[9][10][11][12]. One major reason behind this lack of consistent results is that the vast majority of clinical studies have been relying on serum creatinine concentration (SCrea) as the sole end point [2,9,11,12]. Unfortunately, SCrea is a notoriously poor surrogate marker for glomerular filtration rate (GFR): SCrea is quite insensitive in patients with normal pre-existing GFR and conceals quick and transient changes in GFR such as an immediate drop upon CM administration [2,13,14].…”
Section: Introductionmentioning
confidence: 99%